The nickel output to abyssal pelagic manganese oxides: A balanced elemental and isotope budget for the oceans - Fleischmann, Sarah; Du, Jianghui; Chatterjee, Aditi; McManus, James; Iyer, Sridhar D.; Amonkar, Ankeeta; Vance, Derek (Earth and Planetary Science Letters, 2023)
The development of nickel isotopes as a chemical tracer of past ocean environments requires a sound understanding of the modern oceanic budget. Our current understanding of this budget implies a large elemental and isotope imbalance between inputs to and outputs from the dissolved pool of the ocean. This imbalance is mainly caused by the dominant oxic sink of Ni to Mn oxide-rich sediments. Though the Ni isotope composition of Fe-Mn crusts has previously been used as proxy for the Ni isotope composition of these sediments, crusts and nodules represent a very small part of the total Mn oxide output. Instead, Mn oxide microparticle supply to pelagic and hemi-pelagic sediments dominates the removal of Mn to sediments, but there are very few isotope data for such samples. Here we present the first extensive Ni concentration and isotope dataset from fully oxic Mn-rich pelagic sediments, from 6 different sites across the open Pacific and 10 closely-spaced sites in the Indian Ocean. We also present data for one hemi-pelagic site representing a suboxic setting on the California Margin. Abyssal Pacific and Indian Ocean sediments have a Ni/Mn ratio of 0.02 (similar to Fe-Mn crusts) and their authigenic Ni is isotopically lighter (δ60Ni = +0.26 to +1.08‰) than seawater (+1.33‰) and crusts (+1.55±0.38‰). Data presented here for organic carbon-rich suboxic sediments of the Californian margin have lower Ni/Mn ratios (0.004 to 0.014 for the oxic top of the core, where Mn oxide is present in abundance) and even lighter authigenic Ni isotope compositions (δ60Ni = -0.08±0.11‰). We show that the Ni isotopes of nearly all Mn-rich sediments and deposits analysed to date, including the new data presented here, are correlated with Co/Mn ratios, suggesting that both are controlled by accumulation rate, progressive incorporation of Ni into the metal oxide structure and isotopic re-equilibration between the solid and aqueous phase. At sites where sediments are diagenetically processed, such as the California Margin, differential diagenetic remobilisation of Mn, Ni and Co cause deviations from this correlation. We present a new mass balance calculation that recognises the importance of scavenging of oceanic Ni to Mn oxide-rich proximal hydrothermal sediments, with low Ni/Mn and light isotope compositions. The mass balance produces a budget that can be simultaneously balanced for both amounts and isotope compositions of Ni. This result provides a strong basis for the application of Ni isotopes as records of the evolution of the metal sink from the oxic oceans through Earth history.
Keywords: manganese oxide sink; marine sediments; Ni isotopes; Nickel; Oceanic mass balance